2021
DOI: 10.17323/jle.2021.11735
|View full text |Cite
|
Sign up to set email alerts
|

Previous studies have several limitations …: Indonesian Doctoral Students’, Indonesian Academics’, and International Authors’ Research Gap Strategies in ELT Research Article Abstracts and Introductions

Abstract: Presenting research gap(s) in a research article (RA), particularly in the abstract and introduction, should be considered by authors, since it functions to show the novelty of the research. As there have been limited studies on the possible variations in authors' research gap strategies and the problems in identifying research gaps, this mixed-method study aimed to fill the gaps. Using genre analysis, this study compared the use of research gap strategies in English Language Teaching (ELT) RA abstracts and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 37 publications
(75 reference statements)
0
20
1
Order By: Relevance
“…Among limited studies on writers' strategy in establishing an RG in their article introduction are those conducted by Lim (2012), Suryani et al (2015), Müeller-Bloch and Kranz (2015), Chen and Li (2019) and Arianto et al (2021). Lim (2012) found that compared to writers in Educational Psychology, Second Language Writing, and Biochemistry, more writers in the field of Management indicated their RGs in their article introductions.…”
Section: Writers' Strategy In Establishing Research Gapsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among limited studies on writers' strategy in establishing an RG in their article introduction are those conducted by Lim (2012), Suryani et al (2015), Müeller-Bloch and Kranz (2015), Chen and Li (2019) and Arianto et al (2021). Lim (2012) found that compared to writers in Educational Psychology, Second Language Writing, and Biochemistry, more writers in the field of Management indicated their RGs in their article introductions.…”
Section: Writers' Strategy In Establishing Research Gapsmentioning
confidence: 99%
“…A more recent study on RG strategy in the field of English language education of AL is by Arianto et al (2021). In their study, Arianto et al (2021) compared three groups of writers in AL (i.e., Indonesian doctoral students, Indonesian faculty members, and international journal writers) in the ways they support their research in the article abstracts and introductions.…”
Section: Research Gaps Strategy In the Field Of English Language Educ...mentioning
confidence: 99%
See 3 more Smart Citations